Analysis of KPBU Policy in Using Islamic Financial Instruments in Indonesia - Pamulatsih, Wening; Gultom, Mitra Sami (Sharia Economics Department Universitas KH. Abdul Chalim, Mojokerto, 2024)
The investment target for fulfillment related to infrastructure problems reaches Rp 6445 trillion, Islamic finance focuses on risk sharing, and money management in successful groups. The government must be better able to encourage KPBU to use sharia schemes. Because Sharia-based financing can be divided between the government, private entities, and Islamic financial institutions, it is possible to cover the burden of the government budget. This paper aims to encourage the use of Islamic financial instruments in KPBU projects, to increase the participation of the Islamic financial sector in infrastructure financing in Indonesia.